HUBUNGAN ANTARA KEPEMIMPINAN KEPALA PUSKESMAS DAN KARAKTERISTIK PETUGAS DENGAN KINERJA PETUGAS GIZI PUSKESMAS DI KABUPATEN KARAWANG TAHUN 2007 - Endah Purwanti; Dian Ayubi (Faculty of Public Health, Andalas University, 2008)
Number of malnutrion of children under five year increased in Karawang District during 2001-2006. This situation represents a low performance of nutrient staff. Performance of nutrition staff is related to puskesmas‘s head leadership. This research aim is to assess relationship between performance of puskesmas‘s head leadership with nutrition staff in Karawang. The study design was a cross-sectional study. Total sample was 43 person nutrition staff in all puskesmas in Karawang. Data were analysed using multiple logistic regression. Result of this research found nutrition staff performance shows goodness (55,8%) in general, but management of malnutrition chidren under five years is still unsatisfied. Puskesmas‘s head leadership has a largest association with nutrition staff performace compared to other variables.. Staff who perceived good on puskesmas head leadership will have 13 times greater to have good performencec than staff who perceived poor. Karawang Health District Office should conduct a leadership training for nutrition staff and also for the head of Puskesmas.